(untitled) (Texas Journal of Medical Science, 2022)
An eating disorder (ED) is a mental health illness characterized by abnormal eating styles and behaviors that can affect all people, no matter of their race, age, or habits. Eating disorders behaviors involve abnormal eating behavior and preoccupation with food, attended in most instances by concerns regarding weight and shape